2018
DOI: 10.1002/oby.22148
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Readiness for Adopting Healthy Lifestyle Behaviors Among Indigenous Adolescents with Type 2 Diabetes in Manitoba, Canada: A Cross‐Sectional Study

Abstract: The readiness for adopting healthy lifestyle behaviors is low among adolescents with T2D. Being ready to adopt healthy lifestyle behaviors is associated with better mental health and glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
4
20
0
2
Order By: Relevance
“…Our findings are consistent with the existing literature regarding the challenges faced when intervening on adolescent's health behaviors, though there are several new pieces of knowledge that can be gleaned from the current analyses. Interventions to date most often report that changes in individual diet and activity behaviors may occur within the first few months (3‐6 months) of the intervention, but are not sustained a year or two later . However, such findings are limited by examining behaviors individually; consideration of an individual's patterns of both healthy and unhealthy diet and activity may be more sensitive to evaluating change due to intervention.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings are consistent with the existing literature regarding the challenges faced when intervening on adolescent's health behaviors, though there are several new pieces of knowledge that can be gleaned from the current analyses. Interventions to date most often report that changes in individual diet and activity behaviors may occur within the first few months (3‐6 months) of the intervention, but are not sustained a year or two later . However, such findings are limited by examining behaviors individually; consideration of an individual's patterns of both healthy and unhealthy diet and activity may be more sensitive to evaluating change due to intervention.…”
Section: Discussionsupporting
confidence: 89%
“…This could be possibly due to the adolescent's readiness to adopt lifestyle behaviors at one data collection interval vs the next. A study examining readiness to adopt healthy lifestyle changes in adolescents with T2D found that only 14% of their participants reported being “ready” to adopt such changes . This finding may shed light on the issue that examining behaviors in isolation may be a limitation of existing methods to examine the full impact of lifestyle changes on health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptation of healthy lifestyle behavior may have a significant effect on the diabetes status of a patient. The implementation of healthy lifestyle behavior among adolescent patients means better mental health and good glycemic status ( 36 , 37 ).…”
Section: Methodsmentioning
confidence: 99%